MO514: Cardiorenal Outcomes Associated With Oral Anticoagulant Use in Patients With Atrial Fibrillation. (3rd May 2022) - Mazhar, Faizan; Trevisan, Marco; Hjemdahl, Paul; M. Clase, Catherine; De Jong, Y; Evans, Marie; Bellocco, Rino; Fu, Edouard; Jesus Carrero, Juan
Abstract: BACKGROUND AND AIMS: Novel oral anticoagulants (NOAC) are currently the first-line choice for stroke prevention in patients with atrial fibrillation (AF), as they have a better risk/benefit profile compared with vitamin K antagonists (VKA). Secondary analyses of trials suggest that NOAC also reduces kidney outcomes, but this has been less explored. METHOD: Observational study from the SCREAM project comparing clinical outcomes of all persons with AF and eGFR ≥15 mL/min/1.73 m 2 that initiated NOAC or VKA in Stockholm, Sweden, during 2011–18. The primary outcomes were acute kidney injury (AKI, by diagnosis or sudden creatinine elevation) and the composite of kidney failure and >30% eGFR decline. Secondary outcomes were major bleeding and the composite of hospital admission with stroke or systemic embolism. Inverse probability of treatment weighting (IPTW) was used to balance 51 baseline confounders. Sensitivity analyses included falsification endpoints (pneumonia and cataract surgery), subgroups and evaluation of per-protocol effects. RESULTS: A total of 32 699 patients initiated oral anticoagulants (median age, 75 years, 45% women, median eGFR 73 mL/min/1.73 m 2 ), of which 18 323 (56%) used NOAC. Compared with VKA, initiation of NOAC was associated with a 13% lower relative risk of experiencing the composite kidney outcome (HR: 0.87; 95% CI 0.78–0.98) and a 12% relative risk reduction on AKI occurrence (HR: 0.88; 95% CI 0.80–0.97). Compared with VKA, NOAC use was associated with a lower risk of major bleeding (HR 0.77; 95% CI 0.67–0.89), but a similar risk of stroke/systemic embolism (HR: 0.93; 95% CI 0.78–1.11). Results were similar across subgroups, including patients with chronic kidney disease (eGFR <60 mL/min/1.73 m 2 ) and when censoring patients at treatment discontinuation or switch. CONCLUSION: Compared with VKA, and regardless of baseline kidney function, initiation of NOAC was associated with a lower risk of CKD progression, AKI and major bleeding, but a similar risk of the composite of stroke and systemic embolism.